Conductive Adhesive and Antibacterial Zwitterionic Hydrogel Dressing for Therapy of Full-Thickness Skin Wounds - Wang, Feng; Wang, Shuguang; Nan, Liping; Lu, Jiawei; Zhu, Ziqi; Yang, Jintao; Zhang, Dong; Liu, Junjian; Zhao, Xiao; Wu, Desheng (Frontiers in Bioengineering and Biotechnology, 2022)
Any sort of wound injury leads to destroy skin integrity and wound formation, further leading to millions of deaths every year, accounting for 10% of death rate insight into various diseases. The ideal biological wound dressings are highly expected to possess the extraordinary mechanical characterization, cytocompatibility, adhesive property, antibacterial property and conductivity of endogenous electric current to enhance wound healing process. Recent progresses have demonstrated that biomedical hydrogels can be used as typical wound dressings to accelerate the whole healing process due to the similar composition structure of skin, while are also limited by the ideal biocompatibility and stable mechanical properties. Herein, we designed a new structural zwitterion poly[3-(dimethyl(4-vinylbenzyl)ammonium)propyl sulfonate] (SVBA) into poly-acrylamide network to extend the practical candidates for the field of wound healing, with remarkable mechanical property, stable rheological property, effective antibacterial property, strongly adsorption, high penetrability and good electroactive property. Both in vivo and in vitro evidence monitors the biocompatibility, and strong healing efficiency indicating the poly(AAm-co-SVBA) hydrogels (PAS) become new wound healing candidates for biomedical applications.